Caso Clinico ARP Nº 19: Comunicação Portossistémica Congénita Extrahepática (Malformação de Abernethy) - Cruz, Manuel (2020)
A 4-year-old male child presented was referred to our department with a history of an incidental finding reported on an abdominal ultrasound which was performed during the diagnostic workup of an interauricular communication. The patient was asymptomatic. For further characterization of the aforementioned finding, a contrast-enhanced computed tomography (CE-CT) with multiplanar and maximum intensity projection reformation (MIP) was performed, followed by digital subtraction angiography (DSA).